2000
DOI: 10.1074/jbc.m000044200
|View full text |Cite
|
Sign up to set email alerts
|

The Orientation of Helix 4 in Apolipoprotein A-I-containing Reconstituted High Density Lipoproteins

Abstract: The three-dimensional structure of the high density lipoprotein (HDL) component apolipoprotein (apo) A-I and the molecular basis for its protection against coronary artery disease are unknown. In terms of discoidal HDL particles, there has been a debate as to the orientation of the apoA-I ␣-helices around the disc edge. The "picket fence" model states that the ␣-helical repeats, separated by turns, are arranged parallel to the phospholipid acyl chains of the enclosed lipid bilayer. On the other hand, the "belt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 38 publications
2
47
1
1
Order By: Relevance
“…In addition, we published a series of studies in which various single tryptophan mutants of apoA-I were analyzed in discoidal HDL particles containing phospholipids with quenching groups at various positions along the acyl chain. The results clearly showed that all eight 22-amino acid helices in apoA-I were oriented perpendicular to the phospholipid acyl chains (12,13).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…In addition, we published a series of studies in which various single tryptophan mutants of apoA-I were analyzed in discoidal HDL particles containing phospholipids with quenching groups at various positions along the acyl chain. The results clearly showed that all eight 22-amino acid helices in apoA-I were oriented perpendicular to the phospholipid acyl chains (12,13).…”
mentioning
confidence: 66%
“…Fig. 6 shows a model for apoA-I termed the "Z-belt" (named because of its shape on the edge of the disc), which we proposed to explain the presence of rHDL particles with three molecules on the disc edge (13). The model is attractive from a symmetry standpoint, because all molecules, including a third, can exist in the same conformation with helices in a belt orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was further supported by a more recent study in which Narayanaswami et al (48) examined the ability of spatially defined nitroxide-labeled phosopholipids to quench the fluorescence of unique single tryptophan apoE3 variants in r-HDL. In addition, a large body of evidence indicates that apoA-I in discoidal HDLs adopt conformations consistent with the belt model (49)(50)(51)(52). Since the sequence of apoE is 44% similar to that of apoA-I and has a similar pattern of 11 and 22 amino acid tandem repeat sequences, it is likely that E422k adopts a similar conformation in NLPs.…”
Section: Discussionmentioning
confidence: 98%
“…The general features of the double-belt model, particularly the LL5/5 registry of the two chains ( 19 ), have been confi rmed by multiple laboratories using physical chemical methods (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%